2015
DOI: 10.4326/jjcvs.44.203
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Leiomyosarcoma Originating from the Abdominal Aorta

Abstract: We report an extremely rare case of leiomyosarcoma originating from the abdominal aorta. The patient was a 57-year-old man who had palpable abdominal mass with pain. The symptoms were consistent, and urgent operation was done due to impending rupture of the abdominal aortic aneurysm. The intraoperative findings showed that the mass was a primary tumor of the abdominal aorta, and the histological diagnosis was leiomyosarcoma. It is reported that its prognosis is very poor, but he survived 7.5 years after diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Analyzing the objects which are not included to the GCVS catalog, we found that 3866 objects from our database have detection in at least one molecule (H 2 O, OH and SiO) and have no association with GCVS objects. However, star-forming regions may be also included in our sample, because starforming regions sometimes have color characteristics similar to those of late-type stars (see discussion in Nakashima et al (2015Nakashima et al ( , 2016). Many authors from the database use color criteria in order to select objects for observations and star-forming regions can be present in the observed source sample.…”
Section: Colour-colour Diagramsmentioning
confidence: 99%
“…Analyzing the objects which are not included to the GCVS catalog, we found that 3866 objects from our database have detection in at least one molecule (H 2 O, OH and SiO) and have no association with GCVS objects. However, star-forming regions may be also included in our sample, because starforming regions sometimes have color characteristics similar to those of late-type stars (see discussion in Nakashima et al (2015Nakashima et al ( , 2016). Many authors from the database use color criteria in order to select objects for observations and star-forming regions can be present in the observed source sample.…”
Section: Colour-colour Diagramsmentioning
confidence: 99%